Preschool-based mother-child emotional preparation program improves emotional connection, behavior regulation in the home and classroom: a randomized controlled trial - Welch, Martha G.; Ludwig, Robert J.; Hane, Amie A.; Austin, Judy; Markowitz, Elizabeth S.; Jaffe, Marc E.; Myers, Michael M. (Frontiers in Child and Adolescent Psychiatry, 2023)
We theorized that increasing emotional connection and reducing emotional stress between mother and child at home would reduce dysregulated behavior in the classroom. We tested a novel family-based school intervention aimed at facilitating mother-child emotional connection. This question has gained great importance following the COVID-19 pandemic, as child mental health has been declared a national emergency. Subjects were randomized into two groups; one (Control) receiving the standard curriculum in a large community-based preschool education program, and another (E-Prep) receiving the standard curriculum plus the Emotional Preparation (E-Prep) Intervention. Two to eight E-Prep mother-child pairs participated in eight elective weekly two-hour group sessions over a sixteen-week period. During the two-hour sessions, the pairs were engaged in face to face calming sessions. At six months post-enrollment, we assessed mother-child emotional connection on the Welch Emotional Connection Screen (WECS). In addition, mothers and teachers completed validated questionnaires and instruments. We found that the percentage of E-Prep mother-child pairs who became emotionally connected at six months was five-fold higher than Control pairs (47.4%,vs 8.3% p=0.004, effect size =0.44). Also at six months, E-Prep children had fewer behavioral symptoms (p=0.024) ) (effect size>0.5); fewer autism symptoms (p=0.048) (effect size=0.53); fewer emotional symptoms (p=0.01) (effect size>0.76); better personal, social skills (p=0.045) (effect size=0.51); better executive function (p=0.032) (effect size=0.59). Importantly, teachers reported E-Prep children showed more improved behavior in the classroom, compared to controls. This trial was retrospectively registered (clinicaltrial.gov registry NCT02970565) three months after the start of the first recruitment on April 9, 2019.We will fill this out laterGenerated Statement: No animal studies are presented in this manuscript.Generated Statement: The studies involving human participants were reviewed and approved by Columbia University Medical Center IRB. Written informed consent to participate in this study was provided by the participants' legal guardian/next of kin.